Citra Maskulinitas Tokoh Pria dalam Novel Trauma Karya Boy Candra - Miftahul Jennah; Shinta Nur fadilah; Ryanitha Prameswari; Mohamad Afrizal (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Masculinity is a social construct often internalized in society through various forms, including literary works. This study aims to analyze the representation of masculinity in Boy Candra's novel Trauma, particularly through male characters interacting with the protagonist, Kimara. This research employs the approaches of literary sociology, gender theory, and trauma theory to understand how masculinity is depicted. Data were collected through a critical reading technique applied to the novel's text. The analysis reveals that masculinity is represented in various forms, ranging from emotional dominance to expressions of affection, as well as the influence of trauma in shaping gender dynamics. These findings emphasize that masculinity in Trauma is not an innate trait but a social construct influenced by emotional and social contexts. The study contributes to gender studies and Indonesian literature, while also enhancing readers’ understanding of the complexity of masculinity in literary works.